(3GdQjGVjGJ GdeGdjI (B:s 99 (3JeQjf eMdhd (B/s - (3efUhQ Hf Yha, YHO GdcQjes ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2011)
(3fUhU h JeGQjf Mhd GdaGFOI GdHSjWI h GdaGFOI GdeQcHI , GdNUe , JcGaD GdGhQGb GdJLGQjI , OaYGJ BNQ h Ghd GdeOI , GNJjGQ GdGSJKeGQGJ h GSJgdGc GdbQhVs
Keywords: (3GdQjGVjGJs; (3GdQjGVjGJ(B- (3GdeGdjIs; (3GdeGdjIs